Casing Deformation Response and Controlling Technology Based on Diagnostics of Shale Gas Fracturing Curve - Shen, Cheng; Zeng, Bo; Wu, Jianfa; Song, Yi; Guo, Xingwu; Zhou, Xiaojin; Li, Junfeng (Frontiers in Energy Research, 2022)
Casing deformation (CD) will seriously affect the fracturing progress and stimulation effect of shale gas. Taking 105 gas wells in the Luzhou shale gas area in southern Sichuan as an example, the CD prediction model was established by introducing the fracture operation curve diagnosis method to analyze the changes in net pressure and propagation mode during fracturing. The fracturing stage induced by CD is called the excited (ET) stage, and the fracturing stage that occurs during CD is called the CD stage. It is concluded that the change of net pressure and the propagation mode are coupled with each other. By natural fracture development, formation curvature and horizontal well trajectory, natural fractures and bedding have been active by high fracturing strength, or because of the frequent crossing-layer in single stage, local stress reverse, makes the net pressure decrease and makes the formation in strike-slip stress state to reverse fault stress state, liquid leak-off and blocked fracture propagation time are increased, thus inducing CD. According to the response law induced by CD, the CD pre-control mode is formed, and the CD pre-control technology is established to quantitatively evaluate the wellbore risk and optimize the fracturing operation order and time arrangement. The CD rate is reduced from 56% in the early stage to 20%, and the integrity of the wellbore is guaranteed to be 100%. The method has strong applicability in the field and can be further popularized.